Magneto-optical investigation and hyperfine interactions of copper substituted Fe3O4 nanoparticles. Issue 5 (April 2016) - Amir, Md.; Baykal, A.; Güner, S.; Güngüneş, H.; Sözeri, H.
Abstract: Copper substituted Fe3 O4 nanoparticles (NPs) (Cu x Fe1− x Fe2 O4 (0.0≤ x ≤1.0)) were synthesized by polyol method and the effect of Cu 2+ substitution on structural, magnetic and optical properties of Fe3 O4 was investigated. X-ray diffraction (XRD), Transmission electron microscopy (TEM), Scanning electron microscopy (SEM), UV–Visible spectroscopy and Vibrating sample magnetometer (VSM) were used to study the physical properties of the products. The room temperature (RT) magnetization ( σ – H ) curves revealed the superparamagnetic nature of the products. The extrapolated specific saturation magnetization ( σ s ) decreases from 42.69 emu/g to 14.14 emu/g with increasing Cu content ( x ). The particle size dependent Langevin fit studies were applied to determine the magnetic particle dimensions ( Dmag ). The average magnetic particle diameter is about 9.89 nm. The observed magnetic moments of NPs are in range of (0.61–1.77) µB and rather less than 4 µB of bulk Fe3 O4 and 1 µB of bulk CuFe2 O4 . Magnetic anisotropy was assigned as uniaxial and calculated effective anisotropy constants ( K eff ) are between 10.89×10 4  Erg/g and 26.95×10 4  Erg/g. The average value of magnetically inactive layer for Cu x Fe1− x Fe2 O4 NPs was calculated as 1.23 nm. The percent diffuse reflectance spectroscopy (DR%) and Kubelka–Munk theory were applied to determine the energy band gap ( E g ) of NPs. The extrapolated optical E g values from Tauc plots are between minimum 1.98 eV to 2.31 eV. From 57Fe Mössbauer spectroscopy data, the variation in line width, isomer splitting, quadrupole splitting and hyperfine magnetic field values on Cu +2 ion substitution have been determined. Although, the Mössbauer spectra for the sample x =0.2 and 0.8 are composed of paramagnetic doublets, ferromagnetic sextets were also formed for other products.